![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(5x^3-10x=5x\left(x^2-2\right)=5x\left(x-\sqrt{2}\right)\left(x+\sqrt{2}\right)\)
b)\(-3x^2y^3+6x^3y^2-x^2y^2=-x^2y^2\left(3y-6x+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/2x2-6x3
b/2x2y2-10x3y+4xy2
giải
a/2x2-6x3
=2x2(1-3x)
b/2x2y2-10x3y+4xy2
=2xy(xy-5x2+2y)
tham khảo nhé
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Giải:
1) \(\left(x-6\right)\left(x^2+6x+36\right)-\left(x+4\right)^3=\left(x-2\right)^3+\left(x+5\right)\left(x^2-10x+25\right)-\left(2x^3+6x^2\right)\)
\(\Leftrightarrow x^3-216-\left(x^3+12x^2+48x+64\right)=x^3-6x^2+12x-8+x^3+125-2x^3-6x^2\)
\(\Leftrightarrow x^3-216-x^3-12x^2-48x-64=x^3-6x^2+12x-8+x^3+125-2x^3-6x^2\)
\(\Leftrightarrow-280-12x^2-48x=-12x^2+12x+117\)
\(\Leftrightarrow-280-48x-12x-117=0\)
\(\Leftrightarrow-397-60x=0\)
\(\Leftrightarrow-60x=397\)
\(\Leftrightarrow x=-\dfrac{397}{60}\)
Vậy ...
2) \(\left(2x+3\right)^3-\left(2x+5\right)\left(4x^2-10x+25\right)=\left(6x-1\right)^2-\left(x-2\right)\left(x^2+2x+4\right)+x^3\)
\(\Leftrightarrow8x^3+36x^2+54x+27-\left(8x^3+125\right)=36x^2-12x+1-\left(x^3-8\right)+x^3\)
\(\Leftrightarrow8x^3+36x^2+54x+27-8x^3-125=36x^2-12x+1-x^3+8+x^3\)
\(\Leftrightarrow54x-98=-12x+9\)
\(\Leftrightarrow54x+12x=9+98\)
\(\Leftrightarrow66x=107\)
\(\Leftrightarrow x=\dfrac{107}{66}\)
Vậy ...
![](https://rs.olm.vn/images/avt/0.png?1311)
- 6x2+13x+6
=6x2+9x+4x+6
=3x(2x+3)+2(2x+3)
=(2x+3)(3x+2)
2. 6x2-15x+6
=6x2-12x-3x+6
=6x(x-2)-3(x-2)
=(x-2).3(2x-1)
3. 8x2 -2x-3
= 8x2-6x+4x-3
=2x(4x-3)+(4x-3)
=(4x-3)(2x+1)
4. 8x2-10x-3
=8x2+12x-2x-3
=4x(2x+3)-(2x+3)
=(2x+3)(4x-1)
5. -10x2+4x+6
=-10x2+10x-6x+6
=-10x(x-1)-6(x-1)
=(x-1).(-2)(5x+3)
6. 10x2-28x-6
=10x2-30x+2x-6
=10x(x-3)+2(x-3)
=(x-3).2(5x+1)
6x2 + 13x + 6 = 6x2 + 9x + 4x + 6 = 3x( 2x + 3 ) + 2( 2x + 3 ) = ( 2x + 3 )( 3x + 2 )
6x2 - 15x + 6 = 6x2 - 12x - 3x + 6 = 6x( x - 2 ) - 3( x - 2 ) = 3( x - 2 )( 2x - 1 )
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1.6x\left(x-10\right)-2x+20=0\)
⇔\(6x\left(x-10\right)-2\left(x-10\right)=0\)
⇔ \(2\left(x-10\right)\left(3x-1\right)=0\)
⇔ x = 10 hoặc x = \(\dfrac{1}{3}\)
KL....
\(2.3x^2\left(x-3\right)+3\left(3-x\right)=0\)
⇔ \(3\left(x-3\right)\left(x^2-1\right)=0\)
⇔ \(x=+-1\) hoặc \(x=3\)
KL....
\(3.x^2-8x+16=2\left(x-4\right)\)
⇔ \(\left(x-4\right)^2-2\left(x-4\right)=0\)
⇔ \(\left(x-4\right)\left(x-6\right)=0\)
⇔ \(x=4\) hoặc \(x=6\)
KL.....
\(4.x^2-16+7x\left(x+4\right)=0\)
\(\text{⇔}4\left(x+4\right)\left(2x-1\right)=0\)
⇔ \(x=-4hoacx=\dfrac{1}{2}\)
KL.....
\(5.x^2-13x-14=0\)
⇔ \(x^2+x-14x-14=0\)
\(\text{⇔}\left(x+1\right)\left(x-14\right)=0\)
\(\text{⇔}x=14hoacx=-1\)
KL......
Còn lại tương tự ( dài quá ~ )